Reducing family poverty through an Islamic women’s empowerment strategy in Indonesia: An analytical network process approach - Aas Nurasyiah; Lubna Sarwath; A. Jajang W. Mahri; Ripan Hermawan; Gina Destrianti Karmanto (Universitas Negeri Surabaya, 2022)
This study is intended to develop a strategy for the socio-economic empowerment of women from low-income families based on an Islamic perspective. The research was motivated by Indonesia’s low score on the Gender Inequality Index (GII) compared to other countries, indicating the gap between men’s and women’s empowerment in Indonesia. The percentage of women who become the heads of poor households increases yearly. This qualitative study uses the Analytical Network Process (ANP) to test the social welfare measures for low-income families carried out by governments, Islamic philanthropic institutions, and Islamic microfinance institutions. As many as fifteen respondents involved in the ANP method were experts on the studied problems, namely regulators, practitioners, and academics. The research results indicate that the main priority issue developing women’s empowerment is the development of partnership networks. In the next stage, the experts concluded that business assistance and mental-spiritual development were the main priorities for empowering women and reducing family poverty. The provision of financial access is the last priority. One implication of this study is that the empowerment program for women from low-income families must be holistic, e.g., by forming a Group Lending Model (GLM) with a modification of the majlis ta'lim (Islamic community discussion group).